IMPROVING STUDENTS’ READING COMPETENCY BY USING THE MIND MAPPING TECHNIQUE ON VIII D GRADE STUDENTS OF SMP DWIJENDRA DENPSAR IN THE ACADEMIC YEAR 2018/2019 - Imelda Jaha Baba; I Komang Dedik Susila (Widyasrama, 2020)
This study aims at improving students’ reading competency through the implementation of mind-mapping technique in teaching and learning process. This study is CAR (Classroom Action Research) carried out in two cycles. The subject of the study is 31 students of VIII D Grade of SMP Dwijendra in academic year 2018/2019. The data were collected through observation, interview, and reading test. The procedure of the study involves planning, observation, action, and reflection. The finding shows that students’ reading score improves; the average score on pretest was 60 with classical completeness of 68%, the average score on Cycle I was 69,54 with classical completeness 80,6%, and the average score of Cycle II was 80,13 with classical completeness of 93,5%. It can be concluded that the implementation of mind-mapping technique can improve students’ reading competency of VIII D Grade of SMP SMP Dwijendra in academic year 2018/2019.